A comparison of wave characteristics at Caparica beach, Portugal, using in-situ and transferred wave data - Capitão, R. (2014)
The HIDRALERTA system is current1y being implemented as a novel ear1y warning system to assess the risk of flooding in coastal and port region areas. With forecasted sea wave conditions at coastal and port areas, the system is able to determine the effects of waves in terms of wave overtopping and flooding, to compare those results with pre-specified thresholds, to build alert maps, and, if necessary, to issue alert messages. The system will be applied to two case studies: Praia da Vitória harbor, in Terceira Island, Azores, and Caparica beach, near Lisbon. One of the major inputs of this integrated system is the characterization of sea wave conditions at the site of interest, so that both measured wave data and selected numerical models are used. Numerical models, however, should be calibrated for each area of application. This paper is a contribution to get a better insight of the wave characteristics at one of those case studies, the Caparica beach, to provide adequate calibration of the mentioned numerical models. Therefore, two measurement campaigns were organized at that location, using several instruments. Data was collected and analyzed, then compared with those transferred from the Port of Lisbon wave buoy, by using numerical wave propagation models, which then enabled one to evaluate SWAN's performance and to calibrate some of its parameters. Thus, the paper describes the sea wave characterization using both in-situ data and transferred data from the Port of Lisbon wave buoy, and discusses the SWAN' s strengths and weaknesses to simulate the wave conditions measured at the two above mentioned campaigns.